Explanation:
Hey there!!
The equation is;
![{x}^(2) - 6x + 7 = 0](https://img.qammunity.org/2021/formulas/mathematics/college/r18aa00rq89dk6hj4u6t6nn7de8or3wy1s.png)
Now, Comparing it with ax^2 + bx + c = 0. we get;
a = 1, b= -6 and c = 7
Use quadratic formula.
![x = \frac{ - b + - \sqrt{ {b}^(2) - 4ac} }{2a}](https://img.qammunity.org/2021/formulas/mathematics/college/3hadvqaepwiy2ef7yiv2w4pjjyk1f9m2r0.png)
Put all values.
![x = \frac{ + 6 + - \sqrt{( { - 6)}^(2) - 4 * 1 * 7} }{2 * 1}](https://img.qammunity.org/2021/formulas/mathematics/college/tegi5gnw1zxw3fhk2cifziv50phsj8e3ze.png)
Simplify them.
![x = (6 + - √(36 - 28) )/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/omt0dj3h50eqmg0yhl8zep4vtgwha24g04.png)
![x = ( 6 + - √(8) )/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/rg7vynt678eqtt6spdsri2lamyvr7fzw89.png)
![x = (6 + - 2 √(2) )/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/5beyuvccee1gbzws18d3eekrfgex8la6qp.png)
Taking positive (+).
![x = (6 + 2 √(2) )/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/s56t7i30b2bu6uc041xzz2z4z9ra20i753.png)
Simplifying them.
![x = (2(3 + √(2) ))/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/lgd4izbg2inkdeq5v9iwcfdc1qd4g62v8c.png)
![x = 3 + √(2)](https://img.qammunity.org/2021/formulas/mathematics/college/zdn2scupkftk1vwj7c167zv86mqfuvv3ln.png)
Now, Taking negative (-).
![x = (6 - 2 √(2) )/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/7pl1mtwdswbwpafebq2jqk28r5fkkcz4l5.png)
Simplifying them.
![x = (2(3 - √(2) ))/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/2y3yefv6g9nsaoep0yfw3aia0uahullln5.png)
![x = 3 - √(2)](https://img.qammunity.org/2021/formulas/mathematics/college/ay2dlkjahnaty8yrl8lx32hbutfyhk9go8.png)
Therefore the answer is;
![x = 3 + √(2) \: and \: 3 - √(2)](https://img.qammunity.org/2021/formulas/mathematics/college/vidcwaxjzpx7ooi2wpxtdrqiel8jmm9jbn.png)
Hope it helps...